2017
DOI: 10.1177/1369433217717120
|View full text |Cite
|
Sign up to set email alerts
|

Flutter performance and aerodynamic mechanism of plate with central stabilizer at large angles of attack

Abstract: To analyze the effects of a central stabilizer on the flutter performance at large angles of attack, this study takes the ideal plate as a section of a bridge deck. The aerodynamic characteristics of stationary cross sections are examined using computational fluid dynamics simulations, and the flutter derivatives are extracted by forced vibration. The critical flutter speed of a target bridge is then calculated, and the aerodynamic mechanism of the central stabilizer is discussed from the work done by aerodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…As previous studies have described (Guo et al, 2020; Tang et al, 2018), the movement of vortex formed at the windward side toward the leeward side is the main cause of flutter. When the box girder moves clockwise, the vortex exists on the windward side of the box girder, and when the box girder moves counterclockwise, the vortex just moves to the leeward side of the box girder, and the vortex will promote the rotation of the box girder.…”
Section: Aerodynamic Mechanism Of Thenon-divergent Fluttermentioning
confidence: 57%
“…As previous studies have described (Guo et al, 2020; Tang et al, 2018), the movement of vortex formed at the windward side toward the leeward side is the main cause of flutter. When the box girder moves clockwise, the vortex exists on the windward side of the box girder, and when the box girder moves counterclockwise, the vortex just moves to the leeward side of the box girder, and the vortex will promote the rotation of the box girder.…”
Section: Aerodynamic Mechanism Of Thenon-divergent Fluttermentioning
confidence: 57%
“…Here, α = 0° and −8° which represent the effects of small and large angles of attack, respectively, are taken as the examples. At large angles of attack, the flutter stability of bridge is improved with the increase in stabilizer’s height (Tang et al, 2018), so a larger height of 0.08 B is set first. At small angles of attack, a higher stabilizer may have adverse effects on the flutter stability (Tang et al, 2018), so a lower height of 0.04 B is set first.…”
Section: Flutter Performance Of An Ideal Box Girdermentioning
confidence: 99%
“…At large angles of attack, the flutter stability of bridge is improved with the increase in stabilizer's height (Tang et al, 2018), so a larger height of 0.08B is set first. At small angles of attack, a higher stabilizer may have adverse effects on the flutter stability (Tang et al, 2018), so a lower height of 0.04B is set first. Different heights of the stabilizer will also be considered later.…”
Section: Effects Of a Single Stabilizermentioning
confidence: 99%
See 1 more Smart Citation
“…These vertical stabilizers installed along the bridge span make the truss girder present the characteristics of a bluff body more, calling for further investigations on the vortex-induced vibration. Tang et al (2018) simplified the actual girder as an ideal thin flat plate to analyze the effect of the vertical stabilizer on structural aerodynamic stability and found that higher vertical stabilizers increase the possibility of vortex-induced vibration or galloping. Therefore, it is very necessary to study the performance of vortex-induced vibration of the truss girder with high vertical stabilizers.…”
Section: Introductionmentioning
confidence: 99%